The paradox of gender equality in the arena of cultural beliefs and practices of the people of Kasena Nankana Municipality. - Nyamadi, Victoria Mensah; Affah, Gideon Atigetogum; Nyamadi, Russell Franklin (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Gender equality is a very common mantra in gender studies but its importance can be undermined. Gender stereotypinghas characterised social value in many communities of the north. The focus of this study has been to examine how cultural practices and beliefs in the patrilineal family system dominated by male discriminate against women and female children. Through well-defined research objectives, the study unveiled how cultural practices and beliefs in the Kasena Nankana Municipality impact on gender equality and further marginalize the women in the communities. The studys main finding was that; gender inequalities still pertains in the study area and this is due to cultural ascription of gender roles. The study further highlighted that, gender socialization perpetuates societys expectations of what a woman supposed to do in the societies. The behaviours and attitudes of the women in the communities were also considered under the study to determine whether these behaviours contributed to gender inequality in the communities.